AVALIAÇÃO DE SERVIÇOS DE APOIO NA PERSPECTIVA DO CONTROLE DE INFECÇÃO HOSPITALAR - Ana Lúcia de Melo Leão, Denise Nobre de Souza -; Milca Severino Pereira; Marinésia Aparecida do Prado (Universidade Federal de Goias, 1999)
The quality of the services of support is an important condition for the prevention and control of Hospital Infections (HI). Objective: To identify and to analyse the operation and pattern of quality of the service infrastructure, in relation to the attendance to the requirements for the control of infection into hospital. Methodology: Descriptive and analytic research accomplished at public and private hospitals. Structured interview and checklist obtained the data, both previously validated, applied in supervisors of the services. Result: Were analysed 13 hospitals 62 services and all have a Hospital Infections Control Commission (HICC). The procedures standardisation was related by 78% of the laboratories; 45% of the drugstore; 61% of the nutrition services; 67% of the laundries; 100% of the services of cleaning. The interaction between the support services and the HICC is larger in the public hospitals. Conclusion: more than 50% of the studied hospitals present a good pattern of control of HI in what it means to the support services.